Membentuk Kesalehan Anak Sejak Dini dalam Keluarga Berdasarkan Perspektif Islam - Neni Komalasari; Wahyudin; Sendi Tresa Utami (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2024)
In forming piety in children from an early age in the family according to an Islamic perspective, of course a set of references is needed as a basis for education. Children's education jurisprudence is part of the reference for educating children in the family according to an Islamic perspective so that they can form children's piety from an early age. This research method uses a type of qualitative research sourced from primary and secondary research data. The analysis used is descriptive in form which functions to determine the conclusion of the problem so that a theoretical building is created based on the problem being researched. From the results of this research, it was found that building piety in children from an early age according to an Islamic perspective is through understanding aspects of jurisprudence, morals, and how to interact with children ethically. Parents' piety in educating children is part of the determinant. How do parents protect children before or even after birth, train children from an early age so that children are obedient in worship, provide love and justice to children, and teach children to love the Koran.